Intracranial dissemination in a primary small cell carcinoma of the brain: a case report and literature review - Sun, Yesheng; Zhang, Ying; Li, Ruichun; Cai, Dongpeng; Zhang, Wei; Yang, Zhiqian (Frontiers in Oncology, 2023)
Primary intracranial small cell carcinoma (SCC) is extremely rare with only 8 previously reported cases. We describe a case of primary intracranial SCC with intracranial metastasis. A 46-year-old man presented with decreased vision and a red and swollen left eye. Brain magnetic resonance imaging (MRI) revealed a heterogeneously enhanced tumor on the left frontal lobe. Preoperative systemic computed tomography (CT), MRI, and positron emission tomography (PET)-CT revealed no extracranial tumors. The tumor on the left frontal lobe was excised. Immunohistochemical staining on the excision showed positivity for CD56, synaptophysin (Syn), cytokeratin (CK), and Ki-67 (30%), and negativity for thyroid transcriptional factor-1 (TTF-1), glial fibrillary acidic protein (GFAP), B-cell lymphoma 6 (Bcl-6), multiple myeloma oncogene 1 (MUM-1), C-Myc, Vimentin, P40, P53, CK7, CD3, CD5, CD20, CD79a, CD10, and CD23. The pathological examination strongly suggested that the tumor was a primary intracranial SCC. One year after the surgery, the patient was readmitted with slurred speech and slow movements. Three well-defined tumors were found in the left upper frontal lobe by brain MRI. Tumor resection was then performed. Further immunohistochemical examination of the excised tissue displayed the same pattern as previously, indicating the recurrence of intracranial SCC in the left frontal lobe. The patient received adjuvant chemotherapy and radiotherapy after the tumor resection. At the 2-year follow-up, he remained asymptomatic.